A review of simulation-enhanced, team-based cardiopulmonary resuscitation training for undergraduate students. (November 2017) - Onan, Arif; Simsek, Nurettin; Elcin, Melih; Turan, Sevgi; Erbil, Bülent; Deniz, Kaan Zülfikar
Abstract: Cardiopulmonary resuscitation training is an essential element of clinical skill development for healthcare providers. The International Liaison Committee on Resuscitation has described issues related to cardiopulmonary resuscitation and emergency cardiovascular care education. Educational interventions have been initiated to try to address these issues using a team-based approach and simulation technologies that offer a controlled, safe learning environment. The aim of the study is to review and synthesize published studies that address the primary question "What are the features and effectiveness of educational interventions related to simulation-enhanced, team-based cardiopulmonary resuscitation training?" We conducted a systematic review focused on educational interventions pertaining to cardiac arrest and emergencies that addressed this main question. The findings are presented together with a discussion of the effectiveness of various educational interventions. In conclusion, student attitudes toward interprofessional learning and simulation experiences were more positive. Research reports emphasized the importance of adherence to established guidelines, adopting a holistic approach to training, and that preliminary training, briefing, deliberate practices, and debriefing should help to overcome deficiencies in cardiopulmonary resuscitation training. Highlights: Attitudes of the students toward interprofessional learning and simulation experiences are positive. A holistic approach to training includes the preliminary training, briefing, deliberate practices, and debriefing. It is possible to teach basic knowledge and skills using training methods requiring few resources during teamwork training. Resuscitation-guiding and prompt devices enhance algorithm compliance, and prevent inappropriate shock cycles.